Ultra‐early hematoma growth in antithrombotic pretreated patients with intracerebral hemorrhage. (16th October 2017) - Roquer, J.; Vivanco‐Hidalgo, R. M.; Capellades, J.; Ois, A.; Cuadrado‐Godia, E.; Giralt‐Steinhauer, E.; Soriano‐Tárraga, C.; Mola‐Caminal, M.; Serra‐Martínez, M.; Avellaneda‐Gómez, C.; Jiménez‐Conde, J.; Rodríguez‐Campello, A.
Abstract : Background and purpose: Patients with acute intracerebral hemorrhage (ICH) pretreated with antithrombotic drugs may have increased early hematoma growth, which would increase mortality risk. The effect of antiplatelet (AP) and vitamin K antagonist (VKA) pretreatment on ultra‐early hematoma growth (uHG) and its relationship with mortality in patients with acute supratentorial ICH was analyzed. Methods: This is an observational retrospective study of a prospective register of 197 ICH patients with first computed tomography (CT) scan taken <6 h from ICH symptom onset. ICH volume was calculated by the ABC /2 formula and uHG by the baseline ICH volume/onset‐to‐CT time (ml/h) formula. The uHG analysis took into account the patient's pretreatment (none, AP or VKA) and the relationship between uHG and very‐early (first 24 h) and 3‐month mortality. Results: In the pretreatment group, 50 (25.4%) patients were treated with AP and 37 (18.8%) with VKA. The median (interquartile range 25–75) uHG was 19.7 ml/h (2.9–44.8) for AP pretreated patients, 16.2 ml/h (5.1–42.5) for VKA pretreated patients and 8.4 ml/h (2.4–21.8) for non‐pretreated patients, P = 0.019. The uHG was higher in patients with very‐early [42.1 ml/h (20.1–79.6)] and total 3‐month mortality [28.0 ml/h (15.8–52.5)] compared with survivors [3.9 ml/h (1.5–10.4)], P < 0.0001. Adjusted by ICH severity and previous functional status, uHG was an independent factor related to very‐early ( P = 0.028) and total 3‐month mortality ( P = 0.014). Conclusions: Patients pretreated with antithrombotics have much higher uHG, which would explain the increased mortality in these patients compared to untreated patients.